Optimization of Outdoor Production of Fresh Water Rotifers (Branchionus calyciflorus) - Mangesh M. Bhosale; R. R. Mugale; M. P. Bhendarkar (Journal of Indian Fisheries Association, 2020)
In the present study optimization of freshwater rotifer, Branchionus calyciflorus, culture using Chlorella vulgaris food type was undertaken. C. vulgaris stock was prepared using agar plating method while egg bearing rotifers were procured from the wild. Cement cistern tanks (1000L capacity) were fertilized using ground nut oil cake (250g), urea (10g), single super phosphate (5g) and algae was inoculated on the same day. The highest cell density of C. vulgaris was observed on 5th day onwards (50000 cells/ml) and was maintained by fertilization on every 15th day. Cultured C. vulgaris was exclusively used to feed rotifers at the intervals of 2× and 3× per day. The highest rotifers density was attained in 3×/day feeding tanks (80-150 ind/ml). The stable rotifer population was recorded (130 ind/ml) when the culture was harvested at 30% on 8th day onwards. This study indicated that the quantity of food and eﬀective harvesting rate have significant role on continuous production of rotifers.